Agrarwirtschaft und agrarstruktureller Wandel in Malaysia - Jaschke, Dieter (ERDKUNDE, 1985)
Malaysia, embracing an area of almost 330,000 squarekilometres, has a population of about 14 million inhabitants. Both parts of the country, peninsular Malaysia and the north of Borneo, are situated in the equatorial tropics of South-East Asia. During the colonial period the British regarded the country as a supplier of tropical products for their home industries. The traditional rural economy based on the cultivation of rice was extended by the introduction of the rubber industry. Eventually, natural rubber, mainly cultivated in plantations, became the most important export product. The Malay people, who stuck to their archaic economic and social structures, were not inclined to work on plantations. Alternatively Chinese and Indian contract labourers were invited to take up these jobs. The outcome was a dualistic economic structure corresponding with a dualistic ethnic and spatial pattern. When Malaysia became independent in 1957 the new administration tried hard to overcome the colonial heritage. Their major concern was to reduce the country’s dependence on the exportation of natural rubber and to improve the standard of living of the rural Malay population. Due to economic problems and the increase of population, these objectives could not be realized entirely. Despite of the decline of rubber prices the rubber growing area has been extended. At the same time the palm oil industry has been successfully introduced. Extensive areas of rain forest and bushland have been cleared for the establishment of new rural holdings. It is true, that the spectrum of agricultural production has been diversified and the government’s support of smallholdings has brought about a general improvement of the income of the rural population, but Malaysia’s economy is nevertheless still dependent on the exportation of a few agricultural products. Another problem is the underdevelopment of the Malayan rice industry. In spite of several government programmes and the success of the ’Green Revolution’, they did not manage to modernize the traditional rural structures. A backward rural economy based on the growing of rice still contrasts with the flourishing production of cash crops.